PEMBELAJARAN BASO PALEMBANG ALUS (BEBASO) DI SEKOLAH - Houtman Houtman (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Remember the importance of the role Palembang language, especially bebaso besides as a medium internal communication but also as a medium construction, development, and inheritance culture community from owners of the language in each community members; and pay attention for beginning age classes at elementary level as a productive ages in obtaining language (including Palembang language as a mother tongue), then , the use of intermediate language at that education level should use Palembang language. Giving lessons using intermediate language at beginning levels can be medium for forming self confidence in students. They feel valued, because language that they usually use and as a medium culture socialization that forming their self confidence, used as a medium in knowledge delivery at their school. Besides that, psychologically students feel safe in school and will always ready for accepting lessons. Inability would occur if certain subjects delivered in secondary language that students have not mastered yet. Besides must struggling to understand lesson materials, also at the same time students must pull out all of their potentials to understand language that spoken in delivered lesson materials. Applied concrete that must to do is in the placement form of Palembang language (bebaso) as a subjects and this is appropriately with the substance of the curriculum 2013.